Workshop and Mentoring on the Development of Gamification Based Mathematics Learning Media for Junior High School Teachers in Lhokseumawe City - Amam Taufiq Hidayat; Haves Qausar; Zata Hasyyati; Munzir Absa; Nur Elisyah; Tulus Setiawan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Mathematics learning in schools continues to encounter challenges, particularly related to low student engagement and learning motivation. One contributing factor is the limited utilization of innovative learning media in classroom instruction. Gamification offers an alternative approach by integrating game elements into learning activities to enhance students’ interest in mathematics learning. Nevertheless, teachers in the Junior High School Mathematics Teachers’ Working Group (MGMP) of Lhokseumawe City still face difficulties in developing and implementing gamification-based learning media. Therefore, this community service program aimed to enhance teachers’ pedagogical understanding and technical skills in developing gamified mathematics learning media. The program was conducted on May 15–17, 2026, involving 20 junior high school mathematics teachers and 2 Mathematics Education students as technical assistants. The implementation employed a participatory workshop and mentoring approach consisting of training sessions, media development workshops, learning simulations, and evaluation activities. Participants were guided in developing learning media using digital platforms such as Quizizz, Wordwall, Kahoot, and Gimkit. The results demonstrated that participants were able to develop gamification based mathematics learning media and improve their understanding of gamification concepts, digital platform utilization, and interactive media development. Furthermore, the program strengthened teachers’ motivation and confidence in integrating digital technology into mathematics instruction.